Sublingual allergen immunotherapy for respiratory allergy: a systematic review - Carlos Blanco; Raphaelle Bazire; Laura Argiz; Jenaro Hernández-Peña (BioExcel Publishing Ltd, 2018)
The objective of the systematic review is to provide complete and updated information on efficacy and safety of sublingual immunotherapy (SLIT) formulations for the treatment of allergic respiratory diseases (ARDs). The literature search was conducted on PubMed database, involving double-blind, randomized clinical trials published between January 1992 and 2018, written in English, and performed in humans. The number of articles finally selected for review was 112. Data from the majority of properly controlled clinical trials demonstrate that SLIT is effective not only with short-term use (first year) but also with long-term use (up to the third year of active therapy), for treating ARDs in children and adults. Both continuous and discontinuous schemes of administration showed significant reductions in symptom and medication scores. Moreover, a SLITinduced disease-modifying effect has been documented mainly with grass pollen extracts, since improvement is maintained during at least 2 years of follow-up after a 3-year treatment period. Additionally, allergen immunotherapy should also be considered a preventive strategy, especially for decreasing bronchial asthma incidence in children and adolescents with allergic rhinitis treated with SLIT. This therapy is also safe, producing only a few mainly local and mild-to-moderate adverse events, and usually self-limited in time. The registration and authorization of allergen SLIT preparations (grasses and house-dust mite tablets) as drugs by regulatory agencies, such as the United States Food and Drug Administration (FDA) and the European Medicines Agency (EMA), has represented a landmark in allergy immunotherapy research. Further long-term studies, specially designed with allergens other than grass pollen or house-dust mites, not only in allergic rhinoconjunctivitis but also on asthmatic subjects, as well as studies comparing different administration schedules and/or routes, are required in order to continue the progress in the modern development of this particularly promising therapy.